Analisis Kritis Penerapan Pancasila dalam Pengembangan Hukum Internasional: Perspektif Negara Berkembang (Jurnal Begawan Hukum (JBH), 2024)
This study explores the application of Pancasila principles in the development of international law from the perspective of developing countries. Pancasila, as the foundational ideology of Indonesia, encompasses values that have the potential to enrich the international legal framework, particularly in terms of social justice, humanity, and international cooperation. Through a qualitative approach involving case studies and document analysis, this research examines how Pancasila principles can be integrated into international legal practice, as well as the challenges and opportunities faced by developing countries. The findings indicate that, despite significant challenges related to diplomatic capacity and influence in international forums, Pancasila principles offer opportunities to promote more inclusive and equitable global policies. Recommendations include strengthening diplomatic capacity, enhancing participation in international relations. forums, forming strategic alliances, and effectively advocating Pancasila values. This study aims to contribute to a better understanding of the role of local values in the development of international law and to strengthen the position of developing countries in the global system.